Comparative Evaluation of Stress Distribution Around The Supporting Bone, Abutment, Prosthesis, Using Zirconia And Titanium Implants In The Anterior Maxilla: A Three Dimensional Finite Element Analysis (Bangladesh Journal of Medical Science, 2023)
Objective: The study was designed to evaluate and compare stress distribution intrans cortical section of bone with titanium implant and zirconia implant model under vertical and oblique forces in anterior maxillary region.Materials and Methods: A three‑dimensional finite element model was designed using ANSYS 13.0 software. Around the prepared implant, bone was constructed with definitive differentiation of outer cortical and inner cancellous. Two straight abutment was constructed, crowns of 9mm mesiodistal width and 11mm cervicoincisal length were created and they were cemented with 50 micron meter cemental layer. The bone-implant interface for both the models was bonded, simulating complete osseointegration and the dental implant, abutment and crown were assumed to be connected as a single unit. Force application was performed in both oblique and vertical conditions using 100 N as a representative masticatory force. For oblique loading, a force of 100 N was applied at 45° from the vertical axis. Von Mises stress analysis was evaluated.Results: The results of the study showed cortical stress in the Titanium and Zirconia model under oblique forces were 81.317 MPa and 78.405 MPa, respectively. Cortical stress in the titanium and zirconia implant model under vertical forces was 46.161 MPa and 46.097 MPa, respectively.Conclusion: Results from this study showed the zirconia implant model led to relative decrease in von Mises stress in trans cortical section of bone compared to titanium under vertical and oblique forces in anterior maxillary region.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 521-528